Cryptic speciation in pan-tropical sea urchins: a case study of an edge-of-range population of Tripneustes from the Kermadec Islands. - Bronstein O; Kroh A; Tautscher B; Liggins L; Haring E (Massey University)
Tripneustes is one of the most abundant and ecologically significant tropical echinoids. Highly valued for its gonads, wild populations of Tripneustes are commercially exploited and cultivated stocks are a prime target for the fisheries and aquaculture industry. Here we examine Tripneustes from the Kermadec Islands, a remote chain of volcanic islands in the southwest Pacific Ocean that mark the boundary of the genus' range, by combining morphological and genetic analyses, using two mitochondrial (COI and the Control Region), and one nuclear (bindin) marker. We show that Kermadec Tripneustes is a new species of Tripneustes. We provide a full description of this species and present an updated phylogeny of the genus. This new species, Tripneustes kermadecensis n. sp., is characterized by having ambulacral primary tubercles occurring on every fourth plate ambitally, flattened test with large peristome, one to two occluded plates for every four ambulacral plates, and complete primary series of interambulacral tubercles from peristome to apex. It appears to have split early from the main Tripneustes stock, predating even the split of the Atlantic Tripneustes lineage. Its distinction from the common T. gratilla and potential vulnerability as an isolated endemic species calls for special attention in terms of conservation.